The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1097/01.ju.0000555059.58598.97
|View full text |Cite
|
Sign up to set email alerts
|

Pd04-11 development of an Interaction Taxonomy for Robot-Assisted Surgery: Preliminary Findings

Abstract: estimated on a per-use basis. This was compared to the purchasing price of Isiris.RESULTS: A total of 1775 cystoscopic procedures were performed, and the reusable cystoscope was used for stent removal in 871 cases. The per-use cost for stent removal procedures using the reusable cystoscope was estimated to be $161.85. The per-use purchasing price for the Isiris device is $200. After 704 stent pulls, micro-costing analysis appears to favor the reusable cystoscope compared to the disposable.CONCLUSIONS: Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Some work seems to be on-going in building interaction taxonomies to assist with communication training in RAS, especially between surgeon and the BA. Bisantz et al's (2019) abstract on the analysis of videos of RARP surgery, for instance, concluded that communication is more situation-based than authoritybased. Schiff et al (2016), in gynaecological surgery, surveyed participants' opinion on the quality of communication against outcomes (operative time and blood loss) and found a significant positive correlation, whereupon the communication barriers were more acutely perceived by the operating surgeon and could significantly lead to worse outcomes.…”
Section: Ba As a Distinct Rolementioning
confidence: 99%
“…Some work seems to be on-going in building interaction taxonomies to assist with communication training in RAS, especially between surgeon and the BA. Bisantz et al's (2019) abstract on the analysis of videos of RARP surgery, for instance, concluded that communication is more situation-based than authoritybased. Schiff et al (2016), in gynaecological surgery, surveyed participants' opinion on the quality of communication against outcomes (operative time and blood loss) and found a significant positive correlation, whereupon the communication barriers were more acutely perceived by the operating surgeon and could significantly lead to worse outcomes.…”
Section: Ba As a Distinct Rolementioning
confidence: 99%